If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2h + -7 = 28 Reorder the terms: -7 + -2h = 28 Solving -7 + -2h = 28 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -2h = 28 + 7 Combine like terms: -7 + 7 = 0 0 + -2h = 28 + 7 -2h = 28 + 7 Combine like terms: 28 + 7 = 35 -2h = 35 Divide each side by '-2'. h = -17.5 Simplifying h = -17.5
| x(9+x)=112 | | 4-23=m-9+18 | | -x^2+1=-5x^2+4x | | 4-23-m-9+18m= | | 9+5r-9r= | | 4x-7-7=-1 | | -15+7+n=-4+16 | | -9r+10r= | | 12t^2-t-6=0 | | 16P^2-36=0 | | -10v+6v= | | 3(x+1)=11+3(2x-3) | | 7-7x=111-35x | | 7p-10p= | | 5+3(2x-3)=6x-(x-3) | | 5x(x+4)=(4x+2)(x+4) | | 3x-8=2(5x+3) | | 5x+8=-18-8x | | 7x-x= | | 3k+24=6 | | 5(2x-4)=3(2x-1)-1 | | 10x-3(x-8)=19-(3x-17) | | 52-7x=2x+15 | | -p+10=-25 | | x^2+y^2-10x-14y+70=0 | | -74-9x=7x | | 25-9(x+1)=17+2(4x+7) | | x-9=36 | | 107-3x=15x+25 | | 5(x+4)-3(x-2)=32 | | -46-8x=8x+18 | | 5(6x+4)=4(2x-9) |